1969
DOI: 10.12669/pjms.302.4086
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of retinopathy in patients with diabetes screened by fundus photographs: a study from primary health care

Abstract: Objective: To determine the frequency, severity and risk indicators of diabetic retinopathy (DR) in patients with diabetes attending a primary care diabetes centre. Methods: This observational study was conducted at Diabetic Association of Pakistan - a World Health Organization collaborating center in Karachi, from March 2009 to December 2011. Registered patients with diabetes were screened by two field fundus photographs. Retina specialists graded the signs of retinopathy according to diabetic retinopathy dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
3
10
1
Order By: Relevance
“…There has been a variable prevalence of DR in national studies ranging from 15% to 58%, probably due to the different sample sizes and most of the studies being hospital based. 12–14 In our study, the prevalence of DR was 17% which is comparable to the data available. But our sample size was larger than most of the studies as we screened a large population which has not been done before.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There has been a variable prevalence of DR in national studies ranging from 15% to 58%, probably due to the different sample sizes and most of the studies being hospital based. 12–14 In our study, the prevalence of DR was 17% which is comparable to the data available. But our sample size was larger than most of the studies as we screened a large population which has not been done before.…”
Section: Discussionsupporting
confidence: 87%
“…Previous Fred Hollows Foundation (FHF) projects and other studies have demonstrated that DR is present in up to 30% of persons known to have diabetes. Therefore, it is estimated that in District Hyderabad, there are approximately 58 000 persons at risk of vision loss from DR. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Diabetic Retinopathy (DR) is a well-recognized complication of diabetes mellitus. Out of 39 million global blindness due to various eye diseases, 4.8% (1.8 million) is due to Diabetic Retinopathy (DR) 1 - 3 Nationally every fourth patient with diabetes has some level of DR 4 , 5 with improved care the diabetics are living longer and are exposed to the risk of chronic complications like DR resulting in increasing blindness. Health care providers are exploring ways and means to control blindness due to diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…21 Similarly, previous local study shown advance diabetic eye disease (TRD) to be 2% in type 1 diabetics. 22 This study reported 2.6% of CSME in h type 1 diabetics. Reports from other part of the world demonstrates that 97% type 1 diabetics developed retinopathy after 25 years of disease.…”
Section: Discussionmentioning
confidence: 65%